1990
DOI: 10.1172/jci114656
|View full text |Cite
|
Sign up to set email alerts
|

Role of tumor necrosis factor-alpha in the pathophysiologic alterations after hepatic ischemia/reperfusion injury in the rat.

Abstract: Cytokines are recognized as critical early mediators of organ injury. We attempted to determine whether or not severe hepatic ischemia/reperfusion injury results in tumor necrosis factor-a (TNF-a) release with subsequent local and systemic tissue injury. After 90 min of lobar hepatic ischemia, TNF was measurable during the reperfusion period in the plasma of all 14 experimental animals, with levels peaking between 9 and 352 pg/ml. Endotoxin was undetectable in the plasma of these animals. Pulmonary injury, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
443
3
12

Year Published

1993
1993
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 785 publications
(485 citation statements)
references
References 35 publications
(22 reference statements)
25
443
3
12
Order By: Relevance
“…Various factors such as the reactive oxygen species [19] , platelet-activating factor [20] , thromboxane A 2 [21] , leukotriene B 4 [22] and endothelin-1 [23] have been identified. In addition, inflammatory cytokines like interleukin-1β and tumor necrosis factor-α also play an important role in hepatic ischemia-reperfusion injury [17] . All these substances induce a rise in [Ca 2+ ] i .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Various factors such as the reactive oxygen species [19] , platelet-activating factor [20] , thromboxane A 2 [21] , leukotriene B 4 [22] and endothelin-1 [23] have been identified. In addition, inflammatory cytokines like interleukin-1β and tumor necrosis factor-α also play an important role in hepatic ischemia-reperfusion injury [17] . All these substances induce a rise in [Ca 2+ ] i .…”
Section: Discussionmentioning
confidence: 99%
“…Although the molecular mechanisms of bleb formation are unknown at present, Ca 2+ -dependent disruption of the cytoskeleton is considered to play an important role in the blebbing of plasma membrane [8,9] . Calpain μ, a Ca 2+ -sensitive for m of Ca 2+ -activated neutral protease (EC 3,4,22,17), has been shown to degrade various cytoskeletal proteins such as talin, α-actinin and filamin [10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported that TNF not only has a deleterious effect on hepatocytes but also has damaging pulmonary effects resulting in pulmonary neutrophil sequestration and hemorrhagic edema (42,43). This observation may be of clinical importance especially in the field of transplantation as primary non-function of the graft is associated frequently with the rapid development of pulmonary insufficiency (46).…”
Section: Discussionmentioning
confidence: 99%